The Analysis of Proper Raw Material Inventory Control to Increase Sales Results in the Home Industry of Sihobuk Martabe Tarutung Beans - Indra Veri Nainggolan; Ester Mawar Siagian (Jurnal Mantik, 2020)
This study aims to determine the implementation of raw material inventory control that should be carried out by Home Industy Kacang Sihobuk Martabe Tarutung in the production of Sihobuk Beans. The data analysis method used is descriptive qualitative data analysis, using the economic order quantity method, safety stockt and he reorder point. Based on the analysis of the peanut raw materials purchase for optimal Sihobuk production according to the economic order quantity method during 2019, which was 7,271 kg per order and the frequency of buyers was 2 times, while according to company policy it was 1,000 kg and the order frequency was 12 times. The quantity of safety stock according to the economic order quantity method in 2019 is 291.67 kg while according to company policy it does not exist because the company does not implement a safety stock system in the production process and the point of reordering 330 kg. The analysis it is known that the total cost of inventories according to the economic order quantity is Rp. 2,073,304, while based on company policy the total cost of inventory is Rp. 5,132,000, so that the Home Industy Sihobuk Martabe Tarutung using the economic order quantity method can save an inventory cost of Rp. 3,058,696. The forecast results for the use of raw materials in the Sihobuk Martabe Home Industry for 2020 are 15,090 kg.